A STRUKTUR DESAIN PADA VISUALISASI MOTIF TENUN UMAPURA, ALOR NUSA TENGGARA TIMUR - Rini, Denik Ristya (SENADA (Seminar Nasional Manajemen, Desain dan Aplikasi Bisnis Teknologi), 2020)
Woven fabric is one of Indonesia's traditional fabrics. There are many woven fabric craftsmen in Indonesia. One of the producers of woven fabrics in Indonesia is in the province of East Nusa Tenggara. The province which has 22 regencies, almost all of its regions have the ability to produce woven fabrics. One of the regions producing woven fabric in NTT is the village of Umapura. Umapura village is called a village of a thousand motifs. This is due to the large number of woven motifs created in this village. It is this diversity of motifs that underlies researchers to conduct research on the structure of woven fabric motifs in Umapura. The research method was conducted using descriptive qualitative. Data collection techniques using interviews, observation and documentation. The results of this study stated that the diversity of weaving motifs in Umapura came from the stilation of fauna around the craftsmen and symbols that were considered sacred by the people. The structure of the motif consists of the main motif, additional motifs and filler motifs.